The Architectural Creativity Test Development: A Many Facet Rasch Model Analysis to Establish Inter-Rater Reliability - Niken Titi Pratitis; Urip Purwono (Universitas Ahmad Dahlan, 2018)
This main purpose of this study is to validate the structure of creativity test’s internal consistency in the field of architecture. Method of analysis’s done by Many Facet Rasch Model (MFRM) approach using Facet Program. There were 44 High School students of Public, Private, and Vocational School, also 2nd and 8th semester Architecture College students involved as participants. Three person become raters, and assessed the participants, which consist of two academicians (Architecture lecturers) and one professional Architect. Analysis of Facet Program’s indicates the comparison between exact agreements value and expected agreements value is very small. So that it produce a very high reliability coefficient (> 0.8). The result shows that rater’s interpretation is very good that it can provide stable and consistent evaluation. It also indicates the agreement for evaluation’s score given. Rater’s agreement also strengthen the evidence that constructed items are relevant with measuring attributes and represent overall measurable domains.Keyword : Inter Rater Reliability, Creativity, Architecture